Historic Archaeology and Ethnohistory at Healy Lake, Alaska - Cook, John P. (ARCTIC, 1989)
A habitation site at Healy Lake in eastern Alaska was occupied by Alaskan Natives more or less continuously for more than 10,000 years. After contact, Euro-American traders entering the area in the nineteenth century influenced the subsistence patterns of the Native people to the extent that a Native village evolved at Healy Lake, and this led in turn to the founding of a local trading post - Newton's - at the mouth of the Healy River nearby. In this way, a fixed Native community developed at Healy Lake in the late nineteenth century, with members of this community dealing with early Hudson's Bay and American traders on the Yukon River. In the early twentieth century - some time after 1910 and perhaps not until after 1917 - the community became permanent, and more sedentary, with more focussed trading patterns. Thus, trade became more localized (to Healy Lake and neighboring Tanacross) and Native interests shifted away from the Joseph winter village, and from the Fortymile and Yukon rivers.Key words: Alaska, trading patterns, Healy Lake, habitation, subsistence, village, Natives, traders Mots clés: Alaska, schémas commerciaux, Healy Lake, habitation, subsistance, village, autochtones, commerçants